METAFISIKA SCIENTIA SACRA DALAM LIRIK LAGU “PLASTIK KITA” SEBAGAI KRITIK ATAS MODERNISME - Fachrial, Rizqy Harnanda; Asnawi, Naupal (Multikultura, 2025)
This paper examines the meaning of the song lyrics “Plastik Kita” by the music group Sore from the perspective of perennialism, particularly the metaphysical thought within the esoteric framework of Seyyed Hossein Nasr’s philosophy. The study focuses on the dimensions of meaning and symbolism in the lyrics as an expression of critique toward modernism. By employing a symbolic interpretive approach and esoteric epistemology, this paper explores how the song’s lyrics convey a spiritual message rooted in Nasr’s Divine metaphysical principles. Emphasis is placed on the critique of modern humanity’s detachment from its Divine source, as well as on the affirmation of the need to restore the sacred relationship between humanity, nature, and the Transcendent Reality. The analysis reveals that Plastik Kita serves as a contemporary expression of esoteric wisdom, articulating a profound critique of the spiritual crisis of the modern age.